2019
DOI: 10.1128/jcm.02023-18
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Antifungal Susceptibility Profile of Aspergillus Species: Comparison between Environmental and Clinical Isolates from Patients with Hematologic Malignancies

Abstract: Global data on the epidemiology and susceptibility of Aspergillus are crucial in the management of invasive aspergillosis. Here, we aimed to determine the characteristics of clinical and environmental Aspergillus isolates, focusing mainly on hematologic malignancy patients. We prospectively collected all consecutive cases and clinical isolates of culture-positive proven/probable invasive aspergillosis patients from January 2016 to April 2018 and sampled the air inside and outside the hospital. Cryptic species-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 42 publications
(47 reference statements)
3
23
0
Order By: Relevance
“…Wild-type isolates and mutant isolates with TR34 showed different melting temperatures. In particular, A. tubingensis revealed intrinsically higher azole minimum inhibitory concentrations according to previous studies [2,3,5]. The A. tubingensis-specific primers and probe designed in this study showed that only A. tubingensis was amplified without affecting other Aspergillus in section Nigri.…”
Section: Plos Onesupporting
confidence: 74%
See 4 more Smart Citations
“…Wild-type isolates and mutant isolates with TR34 showed different melting temperatures. In particular, A. tubingensis revealed intrinsically higher azole minimum inhibitory concentrations according to previous studies [2,3,5]. The A. tubingensis-specific primers and probe designed in this study showed that only A. tubingensis was amplified without affecting other Aspergillus in section Nigri.…”
Section: Plos Onesupporting
confidence: 74%
“…The fungal isolates used in this study were representative strains of clinical and environmental isolates stored anonymously, and standard strains including A. fumigatus (ATCC 16424; American Type Culture Collection, Manassas, VA, USA), A. terreus (ATCC 10690), A. flavus (ATCC 16883), and A. niger (ATCC 16888) [2,15]. The representative Aspergillus isolates were selected for each sequence type according to benA and cyp51A sequencing results.…”
Section: Fungal Isolates and Culturementioning
confidence: 99%
See 3 more Smart Citations